2021
DOI: 10.20960/nh.03373
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity on quality of life in overweight and obese children

Abstract: Effects of physical activity on quality of life in overweight and obese childrenEfectos de la actividad física sobre la calidad de vida en niños con sobrepeso y obesidad

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Other studies observed positive results in the quality of life after the intervention through sports practice. Aguilar-Cordero et al [ 35 ], in a clinical trial with obese Spanish children, observed improvements in physical and mental components related to quality of life (using the SF-10 questionnaire). A 22-week intervention in aerobic and resistance training groups of adolescents showed significant increase in quality of life when compared to controls, being quality of life assessed by Pediatric Quality of Life questionnaire [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies observed positive results in the quality of life after the intervention through sports practice. Aguilar-Cordero et al [ 35 ], in a clinical trial with obese Spanish children, observed improvements in physical and mental components related to quality of life (using the SF-10 questionnaire). A 22-week intervention in aerobic and resistance training groups of adolescents showed significant increase in quality of life when compared to controls, being quality of life assessed by Pediatric Quality of Life questionnaire [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that an intervention program that includes obesity-related health education, physical activity, and diet control is important to improve HQOL in the child, especially in boys [56]. Also, the HQOL seems to be benefited from an educational intervention program focused on physical activity and nutritional recommendations in children and adolescents with obesity [57].…”
Section: Discussionmentioning
confidence: 99%
“…Authors such as Aguilar Cordero et al 13 affirm that the most effective physical activity program in overweight and obese adolescents is the one that combines aerobic and anaerobic exercises. Therefore, this study confirms that the virtual physical exercise program applied to the experimental group it was designed with aerobic and anaerobic exercises with moderate and vigorous intensity.…”
Section: Discussionmentioning
confidence: 99%
“…It is proven that the combination of both helps reduce overweight and obesity and improves schoolchildren’s physical condition and motor development. 13…”
Section: Methodsmentioning
confidence: 99%